Pengembangan Kompetensi Siswa dalam Pembelajaran dengan Menggunakan Metode Game-Based Learning - Nicholas Patrick Varian; Binastya Anggara Sekti (Ikatan Ahli Informatika Indonesia, 2024)
Learning in classrooms is often seen as dull and lacking interaction, leading students to lose interest in understanding the material. To combat this, new teaching methods have been introduced, including interactive learning through games. Despite games' potential to boost motivation and engagement, further research is needed to understand Game-Based Learning's (GBL) specific impact on learning experiences, competency development, and student achievements. This study employs a quantitative approach, collecting data via surveys and tests on students using GBL. Hypotheses are tested through statistical analysis. Results reveal GBL's positive influence on students' learning experiences, with increased motivation, engagement, and comprehension of material. GBL also enhances students' competencies and improves learning outcomes. Thus, GBL emerges as an effective method for enhancing learning experiences, developing student competencies, and boosting academic achievements. Integrating GBL into educational curricula is crucial for improving learning quality and student outcomes.